What man does, or can and should do of himself. Pragmatic anthropology and moral philosophy Kant - Saldarriaga Madrigal, Andrés (Estudios de Filosofía, 2015)
This paper tries to determine, within the Kantian corpus, the relationship between of Anthropology in the pragmatic sense, and the so-called works that state the basis of morality. The central thesis is that Anthropology is an essential part of the Kantian theory of morality, despite the fact that it is a radically different theoretical part of it, precisely because it is not reduced to the means or purposes of moral theory. The function of Anthropology would be to illustrate the principle of morality by collecting and analyzing the visible signs of freedom. In this way Anthropology could be considered a semiotics of freedom. This text presents the limits of the pragmatic approach but also the possibilities it offers for philosophical anthropology in general.